2005
DOI: 10.1002/elps.200410427
|View full text |Cite
|
Sign up to set email alerts
|

BRAF mutation detection and identification by cycling temperature capillary electrophoresis

Abstract: BRAF mutations are found in many human tumors, namely melanomas ( approximately 70%) and colon carcinomas ( approximately 15%). This paper presents a method for identification of exon 15 BRAF mutations by denaturant capillary electrophoresis (CE), an analysis method that is sensitive, cost-effective (involving only polymerase chain reaction (PCR) and electrophoresis) and capable of high-throughput screening. In total, we found 21 (70%) out of 30 melanoma cell lines with BRAF mutations in exon 15: two of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…Although some have argued that RAF1 inhibits BRAF activation in a kinase domaindependent fashion (19), other studies reported that human cancer-associated BRAF mutants with impaired kinase activity promote MEK activation by binding to and trans-activating RAF1 (12,51). Of note, these kinase-impaired mutations alter the activation segment of BRAF, and some (D594G and T599I) are analogous to NS-associated RAF1 mutants (16,18). Heidorn and colleagues recently reported that mice with a conditional kinase-dead Braf (Braf LSL-D594A ) allele, when combined with oncogenic Ras (Kras G12D ), induced melanomas in mice.…”
Section: Raf1mentioning
confidence: 99%
“…Although some have argued that RAF1 inhibits BRAF activation in a kinase domaindependent fashion (19), other studies reported that human cancer-associated BRAF mutants with impaired kinase activity promote MEK activation by binding to and trans-activating RAF1 (12,51). Of note, these kinase-impaired mutations alter the activation segment of BRAF, and some (D594G and T599I) are analogous to NS-associated RAF1 mutants (16,18). Heidorn and colleagues recently reported that mice with a conditional kinase-dead Braf (Braf LSL-D594A ) allele, when combined with oncogenic Ras (Kras G12D ), induced melanomas in mice.…”
Section: Raf1mentioning
confidence: 99%
“…The standard test currently employed to analyze patients' biopsies before initiation of vemurafenib treatment relies on real time PCR (the COBAS TM Test 10 ), whereby 5-10% of BRAFmutated melanoma cells can be detected in a background of normal cells. Alternative technologies to classic methods are under development, such as cycling temperature capillary electrophoresis 11 with sensitivity comparable to COBAS TM , silicon nanowire field-effect transistors 12 and a threedimensional gold nanowire platform 13 . The latter technologies have only been shown to work using synthetic oligonucleotide targets, larger gene fragments or still rely on an initial PCR amplification.…”
mentioning
confidence: 99%
“…Most recently we have illustrated how the Ekstrøm's laboratory development of cycling denaturing capillary electrophoresis (CyDCE) eliminated the labor-intensive optimization steps attendant on constant denaturing systems. 26,74,76,[81][82][83][84] .…”
Section: Applications In Human Dna Cells Tissues Tumors and Populamentioning
confidence: 99%
“…The data is then plotted as midpoint temperature versus the base sequence, creating a melting profile of the fragment 87 . The goal of melting profile analysis of DNA fragments with computer programs prior to DCE is to select and manipulate the target sequence, attach GC-clamp if necessary, so that the region of interest is in a low melting domain adjacent to a sequence with high temperature melting properties 28,53,82,87,[89][90][91] . The introduction of the thermally stable clamp increases the percentage of detectable DNA variants in the low melting domain by DGGE to close to 100% 92,93 .…”
Section: Design Of Dna Amplification Fragments With Appropriate Meltimentioning
confidence: 99%
See 1 more Smart Citation